Alpha-Adrenoceptor Blockade as a Novel Pathway Toward Non-Hormonal Male Contraception: A Mechanistic and Clinical Evidence Review - Alicja Roztocka; Patryk Osiński; Halina Car; Natalia Nazarko; Ewa Katarzyna Czech; Emilia Sokołowska (Journal of Clinical Medicine, 2026)
Alpha-1 adrenergic receptor antagonists are widely used in the management of lower urinary tract symptoms, where they can induce ejaculatory dysfunction as a pharmacodynamic effect, particularly with α1A-selective agents. This observation has led to growing interest in their potential role as non-hormonal male contraceptives. This narrative review evaluates current clinical and preclinical evidence regarding the impact of α-blockers on the ejaculatory mechanism, with a focus on their potential application in male contraception. Both human and animal data were examined to contextualize the mechanistic basis for contraceptive potential. Evidence from clinical and pharmacological studies indicates that inhibition of α1-adrenoceptor-mediated smooth-muscle contraction in tissues involved in seminal emission, including the vas deferens, seminal vesicles, and prostate, can impair the emission phase of ejaculation. Agents such as tamsulosin and silodosin have been reported to induce anejaculation or markedly reduce semen volume, providing pharmacodynamic evidence of impaired seminal emission; however, these effects should not be considered equivalent to demonstrated contraceptive efficacy. Prospective clinical evidence currently includes one prospective pilot study and one randomized placebo-controlled clinical trial evaluating silodosin as a potential reversible non-hormonal male contraceptive. The prospective evidence includes marked and progressive suppression of sperm output and semen volume with repeated silodosin administration; at week 12, 94% of participants achieved a total sperm count ≤ 1 × 106 per ejaculate, while the observed pregnancy incidence was 4% versus 17% with placebo. However, the available evidence remains insufficient to establish reliable contraceptive effectiveness for individual sexual exposures. Safety considerations, including cardiovascular effects and sexual dysfunction, also remain insufficiently characterized in healthy men. α1-adrenoceptor antagonists represent a biologically plausible pharmacologic strategy for male non-hormonal contraception by interfering with seminal emission and sperm delivery without directly suppressing spermatogenesis. Further pharmacokinetic–pharmacodynamic studies and rigorously designed multicentre clinical trials are required to determine the optimal dosing strategy, completeness and consistency of seminal emission suppression, contraceptive effectiveness, safety, acceptability, and reversibility of this approach.